KAJIAN PLAGIARISME: Studi Perbandingan Hukum Islam dan Hukum Positif di Indonesia - Alfarisi, Usman (Jurisdictie: Jurnal Hukum dan Syariah, 2018)
Allah swt blesses human on earth by giving them mind. However, not every human is willing to think. In the field of education, laziness often leads to plagiarism that violates the copyright and is against the norms of Islamic law and sharia purposes (Maqashid al Syari'ah). This study aims to review plagiarism in Indonesian and Islamic laws as well as its sanction. This is a normative research with qualitative approach. The data were obtained through the documentation. The study indicates that Indonesian and Islamic laws are on the same line judging plagiarism. Both laws agree that it is the act of criminal that is harmful to other people. Coping with that, the doer is punished with administrative sanction, paying fine, or putting in prison. In Islam, plagiarism is not included in hudud or qishash, thus ta’zir is seen proper to punish the doer. It is done by giving them warning, paying fine, sending in to prison, or other sanctions decided by the man of power. To sum up, the regulation about plagiarism in Indonesia is not against Islamic law.